Downhill running: strategies to improve performance - Vernillo, G. (8th International Congress Mountain Sport & Health. Updating Study and Research from Laboratory to Field. 7-8 November 2019, Rovereto (TN) - Italy. Programme and Book of Abstracts, 2019)
Downhill running is characterized by larger eccentric contractions of lower-limb extensor muscles, greater impact shocks and ground reaction forces. Considerable mechanical stress is then placed on the lower-limb muscles (particularly the knee extensors and plantar flexors) as a result of the repeated eccentric contractions necessary for controlling the descent on steep gradients during downhill running.This may induce lower limb tissue stress, short-term neuromuscular fatigue, and/or muscle damage. The combination of high-mileage and large sections of downhill running associated with trail and ultratrail racing has been hypothesized to induce deleterious alterations in the neuromuscular, energetic, biomechanical, and skeletal-muscle oxygenation response.In downhill running, muscle fatigue and skeletal muscle damage is compensated by a greater neural input to the muscle to produce the same amount of force, particularly during the push-off phase of the running cycle. This increased neural input to the muscle may results in higher O2 demand and consequently a poorer running economy. Among all known strategies to attenuate the negative effects of downhill running, training seems to be the best option. Indeed, several studies have demonstrated that an a priori bout of eccentric exercise produces protective adaptations such that, after a subsequent bout of similar exercise (the so-called repeated bout effect), neuromuscular function adapts (e.g. muscle and neural adaptations) such that it is partially protected from subsequent damaging stimuli. However, the specific applications for trail and ultratrail training are still scanty and there is the need to assess the effectiveness of training strategies to minimize fatigue and damage. This would have important implications for trail and ultratrail runners in order to minimize the deleterious effects of downhill running and, therefore, to better model training and running technique prescriptions with the ultimate goal of improving the trail and ultratrail performance.